Short Communication: Callus induction in purple and white-purple varieties of Orthosiphon aristatus (Blume) Miq. - Fahrauk Faramayuda; TOTIK SRI MARIANI; ELFAHMI ELFAHMI; SUKRASNO SUKRASNO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Faramayuda F, Mariani TS, Elfahmi, Sukrasno. 2020. Short Communication: Callus induction in purple and white-purple varieties of Orthosiphon aristatus (Blume) Miq. Biodiversitas 21: 4967-4972. Orthosiphon aristatus (Blume) Miq. are known to have many benefits, including stimulating urine expenditure (diuretics) and dissolving kidney stones. O. aristatus widely planted in Indonesia are purple and white-purple. The main secondary metabolite components of O. aristatus are sinensetin, rosmarinic acid, and eupatorin. One of the initial steps to increase secondary metabolites in O. aristatus is by induction of callus using plant tissue, which later can be developed into a culture suspension for secondary metabolites. The materials used are the leaf of two varieties of O. aristatus that have been sterilized and grown on Murashige and Skoog media with growth regulatory 2,4-dichlorophenoxyacetic acid at a concentration of 0.4;1.0; 2.0 mg/L. The identification of secondary metabolites of callus was carried out by thin-layer chromatography. The best growth regulating agent for callus induction on the leaves of purple and white-purple varieties of O. aristatus is 2,4-D 0.4 mg/L on Murashige and Skoog media. These media can grow callus at a faster time, friable, and slightly white-yellow color. The identification of secondary metabolites in callus acetone extract showed the presence of sinensetin and rosmarinic acid.